An Analytical Study Of Pakistan Tehreek-e-Insaf’s Foreign Policy Towards Afghanistan (2018 – 2022) - Iftikhar Ahmad; Naveed Iqbal; Muhammad Zakaria Niazi (Scholar Insight Journal, 2026)
This study examines Pakistan’s foreign policy towards Afghanistan during the Pakistan Tehreek-e-Insaf (PTI) government from 2018 to 2022. The PTI administration played a pivotal role in Pakistan’s diplomatic engagement with Afghanistan, including the Doha Agreement 2020 and the withdrawal of NATO forces. The research situates Pakistan’s policy within its historical and regional context to assess evolving cross-border dynamics. A qualitative research approach was adopted, including Primary data from official statements by the Ministries of Foreign Affairs of Pakistan and Afghanistan, as well as reports from Dawn and Tolo News. Secondary sources comprised academic journals, books, research articles, dissertations, and newspapers. The data were analyzed using a systematic six-step thematic analysis framework. The findings indicate that the PTI government prioritized peacebuilding, regional stability, economic cooperation, and counter terrorism efforts. Challenges such as economic mismanagement and institutional weaknesses persisted. The study concludes that Pakistan’s foreign policy under the PTI administration was comparatively more coherent and proactive, emphasizing the importance of peace in Afghanistan for enduring stability in Pakistan.